Identification of potential biomarkers and immune infiltration characteristics in recurrent implantation failure using bioinformatics analysis - Lai, Zhen-Zhen; Zhang, Jie; Zhou, Wen-Jie; Shi, Jia-Wei; Yang, Hui-Li; Yang, Shao-Liang; Wu, Jiang-Nan; Xie, Feng; Zhang, Tao; Li, Ming-Qing (Frontiers in Immunology, 2023)
Recurrent implantation failure (RIF) is a frustrating challenge because its etiology remains largely unknown. The present study aims to identify the differentially expressed genes (DEGs) in the endometrium on illustrating immune cell infiltration characteristics between patients with RIF and healthy controls and to explore potential prognostic markers in RIF. Firstly, GSE103465, and GSE111974 datasets were obtained from the Gene Expression Omnibus database to screen DEGs between RIF and the control groups, in which 122 downregulated and 66 upregulated DEGs were identified. Then, Gene Ontology analysis, Kyoto Encyclopedia of Genes and Genomes Pathway analysis, Gene Set Enrichment Analysis, and Protein-protein interactions analysis were conducted to explore the potential biological functions and signaling pathways. Moreover, CIBERSORT was performed to describe the immune infiltration level in RIF, and then flow cytometry was used for verification for the top two most abundant immune cells detected. Through our analysis, we identified 6 immune-related hub genes which were found to be involved in Wnt/β-catenin signaling and Notch signaling. By constructing the ROC curves, 3 (AKT1, PSMB8, and PSMD10) out of the 6 identified genes showed potential diagnostic values for RIF. Ultimately, we attempted to uncover potential therapeutic or induced compounds for RIF by cMap analysis, among which fulvestrant (estrogen receptor antagonist), bisindolylmaleimide-ix (CDK and PKC inhibitor) and JNK-9L (JNK inhibitor) were speculated to influence interfere with the pathogenic process of RIF. Moreover, our data revealed the immune infiltration level in highlighting 3 signaling pathways (Wnt/β-catenin signaling, Notch signaling, immune response) and 3 potential diagnostic DEGs (AKT1, PSMB8, and PSMD10) in RIF. Importantly, our findings may help to provide a scientific basis for several possible therapeutic agents to ameliorate endometrial receptivity.